(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2017)
The aim of the article is an appraisal of possible uses of straw for energy purposes in pomorskie voivodeship. The article assessed: production, agricultural demand, straw energy potential and its surplus. The research of energy potential was conducted in pomorskie voivodeship districts. The research shows that straw surplus for energy purposes is equal to 1 M tones which could provide 10,4 thousand TJ of energy annually. The highest straw energy potential is characterized by słupski, sztumski, tczewski, malborski, człuchowski and nowodworski districts. While the lowest energy potential is characterized by lęborski, pucki, kościerski, chojnicki and kartuski ditricts.